Mutation spectrum of NDP, FZD4 and TSPAN12 genes in Indian patients with retinopathy of prematurity. Issue 2 (5th October 2017) - Rathi, Sonika; Jalali, Subhadra; Musada, Ganeswara Rao; Patnaik, Satish; Balakrishnan, Divya; Hussain, Anjli; Kaur, Inderjeet
Abstract : Aim: Retinopathy of prematurity (ROP) is a vasoproliferative eye disease in preterm infants. Based on its phenotypic similarities with familial exudative vitreo retinopathy (FEVR), the present study was conducted to screen the Norrin signalling pathway genes (already been implicated in FEVR) for understanding their involvement among Indian patients with ROP. Methods: The study cohort consisted of patients with ROP (n=246) and controls (n=300) that included full term (n=110) and preterm babies devoid of ROP (n=190). Screening of the NDP, FZD4, TSPAN12 genes were accomplished by resequencing the entire coding and untranslated regions (UTR). The genotype data of the patients with ROP were analysed in the background of their clinical manifestations and further analysed in conjunction with other available data on these genes worldwide. Results: Two novel variants in intron 1 (IVS1 +16A>G) and 3′UTR (c.5 22T>C) along with a previously reported change in the 5′UTR (c.395_409del14bp) were observed in the NDP gene in three patients with ROP. Screening of the FZD4 revealed four heterozygous variants, p.(Pro33Ser), p.(Pro168Ser), p.(Ile192Ile) and p.(Ile360Val), a compound heterozygous (p.(Pro33Ser)/p.(Pro168Ser)) and a 3′UTR (c*G>T) variants in the study cohort. Variants p.(Pro33Ser) and p.(Pro168Ser) were found to be significantly associated with ROP. A heterozygous variant p.(Leu119Arg) in TSPAN12 gene was observed in a patient with threshold ROP. However, a formal genotype–phenotype correlation could not be established due to the low frequencies of the variant alleles in these genes. Conclusions: This is a first study that revealed association of few variants in Norrin signalling genes among Indian patients with ROP that warrants further detailed investigation worldwide.